Trade and deforestation: A literature review - Juan Robalino; Luis Diego Herrera (World Trade Organization (WTO), 2010)
Forest plays a significant role in the overall balance of carbon in the atmosphere. Forest carbon sequestration can potentially reduce the accumulation of greenhouse gases in the atmosphere. However, when deforestation takes place, carbon is released to the atmosphere again. Globally, it has been estimated that about 11% to 39% of all carbon emissions from human origin come from the forest sector (Hao et al. 1990). Regarding global warming, the balance between forest conservation and deforestation can change forest sector activities from a solution to a problem and vice versa.
Keywords: 330; Abholzung; Außenwirtschaft; Welt